TH7.11 Developing a new TAMIS service at a district general hospital. A dual consultant experience. (9th August 2022) - Lord, Ian; Ward, Nicholas; Mishra, Ami
Abstract: Aim: To evaluate the development of a Transanal Minimal Access Surgery (TAMIS) service at a district general hospital. Method: In 2017, a TAMIS service was set up at our hospital by 2 consultants trained in single port laparoscopic and transanal endoscopic techniques. Benign rectal polyps and early cancer cases were performed as dual consultant procedures. All cases were reviewed in the colorectal MDT pre-operatively. Data was collected prospectively for patient demographics, co-morbidity, length of stay, complications, pathology and surveillance outcomes. Results: Between May 2017 and July 2021, 31 TAMIS procedures were performed. The median age was 73(34–87) with 17(55%) male and 14(45%) female patients. The indication for resection was adenomatous polyps in 20(65%) patients and adenocarcinoma in 11 (35%) patients. The median diameter of benign polyps was 44mm(25–105mm). At a median follow up of 8 months (0–48 months) there were no recurrent polyps. Rectal cancers had a median size 23mm (11–32mm). Nine cancers were T1 (82%), one T2 (9%), and one T3(9%). All cancers were R0 resections. At a median follow up of 15 months (3–43) there were no locoregional or distant recurrences. The median length of stay was 1 day (0–2). There was no post operative mortality. The readmission rate was 5% with two Clavien-Dindo grade 1 complications. Conclusions: Dual consultant operating in the early phase of this service's development has allowed for experience to be concentrated and shared problem solving, resulting in encouraging early outcomes with no local recurrence, short inpatient stay and minimal morbidity.